Evaluasi Toksisitas Teratogenik Buah Beligo (Benincasa hispida (Thunb.) Cogn.) Terhadap Fetus Mencit Bunting - Nur; Mustaina; Jumrah Sudirman; Emilina Jafar (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
The use of drugs during pregnancy can cause problems for the fetus. Prolonged use of synthetic drugs and herbal products risks causing accumulation in the fetus, while the fetus does not yet have a perfectly functioning metabolic system, which has the potential to cause teratogenic effects. Beligo (Benincasa hispida (Thunb.) Cogn.) is a plant that has the potential to be developed as a herbal medicine. This study aims to determine the teratogenic effect of ethanol extract of beligo fruit on the fetuses of female mice. The method included extraction by maceration and teratogenic effect testing using 16 mice, which were divided into four treatment groups—group I was given Sodium Carboxymethyl Cellulose (Na-CMC) 1% and groups II, III, and IV were given ethanol extract of beligo fruit flesh at doses of 140 mg, 280 mg, and 560 mg/kg BW, respectively, orally. The results showed that the ethanol extract of beligo fruit flesh at 140 mg, 280 mg and 560 mg/kgBW in mouse fetuses was 100% complete same with Na-CMC 1% as a negative control. In conclusion, the ethanol extract of beligo fruit at 140 mg, 280 and 560 mg/kgBW had no teratogenic effect.